Navigating Language Diversity In Multilingual Stem Classrooms: Strategies For Inclusive Education - Mokikwa, Hamza; Mokhele-Ramulumo, Moleboheng (International Education Trend Issues, 2024)
In multilingual STEM classrooms, language diversity presents challenges and opportunities for inclusivity. This study examines the impact of language diversity on STEM education, emphasizing its relevance in a globalized context. By employing a mixed-methods approach, including surveys and interviews with students, educators, and administrators, we identify patterns in the interplay between language diversity and inclusive education. Preliminary findings highlight challenges such as communication barriers and opportunities for enriched problem-solving. The discussion emphasizes recognizing linguistic diversity as an asset and suggests strategies to address barriers, advocating for a supportive, inclusive classroom. Implications for educators, policymakers, and researchers underscore leveraging linguistic diversity as a strength, with recommendations including professional development, integrating diverse perspectives into STEM materials, and implementing inclusive language policies for a more equitable STEM education landscape.